The skeletonised right gastroepiploic artery for coronary artery bypass grafting: A case report - Naidoo, S. (SA Heart Journal, 2025)
Coronary artery bypass grafting(CABG) has been the mainstay for treating multivessel coronary artery disease for many decades. Various conduits have been studied to optimise surgical outcomes of CABG. The gastroepiploic artery(GEA) has been used as an in-situ graft for over 30 years. Multi- and total arterial revascularisation using the internal thoracic artery, radial artery, and GEA grafts are an option for better outcomes.